Hubungan Pengetahuan Remaja Putri tentang Personal Hygiene dengan Kejadian Keputihan - Yefan Adji; Siti Hadija Batjo; Hastuti Usman (Poltekkes Kemenkes Palu, 2019)
Leucorrhoea is a clinical disorder that is often complained of by all women. For young women who are just entering puberty with all forms of phenomenal changes in themselves, this problem will have a negative impact in the future if it is not addressed early. The purpose of this study was to determine the relationship of adolescent girls' knowledge about personal hygiene with Leucorrhoea. This research was an analytic research with a cross-sectional approach. The population of this study was 36 female students in class X and class XI in Pagimana I Senior High School. The sampling technique used purposive random sampling. The results were obtained by 33 knowledgeable (91.7%). Adolescents who have good knowledge and experience Leucorrhoea as many as 19 people (57.6), who do not Leucorrhoea 14 people (42.4%), who lack knowledge and experience Leucorrhoea as much as two people (66.7%), who do not have Leucorrhoea as much as one person (33.3%). Chi-square test showed p-value=1,000. The conclusion of the study, there is no relationship between the knowledge of adolescent girls about personal hygiene with Leucorrhoea. Suggestions for adolescent girls to maintain good personal hygiene to prevent Leucorrhoea.